Diagnostic value of laboratory results in children with acute appendicitis - Tartar, Tugay; Bakal, Unal; Sarac, Mehmet; Aydin, Suleyman; Kazez, Ahmet (Walter de Gruyter Gmbh, 2020)
Background: The correct diagnosis rate in acute appendicitis (AA) is between 72 and 94% despite advanced laboratory and radiologic examinations. This study was conducted to determine the effectiveness of laboratory parameters in the diagnosis of children with appendicitis. Materials and methods: Patients who underwent appendectomy were divided as AA (subdivided into two groups as perforated and non-perforated) and without appendicitis. White blood cell (WBC), neutrophil-to-lymphocyte ratio (NLR), red cell distribution (RDW), mean platelet volume (MPV), C-reactive protein (CRP), procalcitonin levels and Alvarado score were recorded. Results: WBC, NLR and CRP levels were higher in patients with AA (p<0.05). According to the receiver operating characteristic (ROC) curve, area under the ROC curve (AUC), p values and 95% confidence interval in predicting patients with and without appendicitis were NLR: 0.703, 0.025, 0.523-0.884; CRP: 0.822, <0.001, 0.725-0.919; procalcitonin: 0.631, 0.150, 506-0.755 and Alvarado score: 0.754, 0.05, 0.578-0.930, respectively. RDW, CRP and procalcitonin values of perforated appendicitis patients were higher compared with those of the non-perforated ones (p<0.05). According to the ROC curve, AUC, p values and 95%CI were NLR: 0.583, 0.094, 0.488-0.678; RDW: 0.715, <0.001, 0.628-0.802; CRP: 0.900, <0.001, 0.842-0.958; procalcitonin: 0.865, <0.001, 0.799-0.930 and Alvarado score: 0.727, <0.001, 0.641-0.812, respectively. Conclusions: CRP is the most effective bioindicator in the diagnosis of AA, the detection of perforated cases. It was revealed that NLR is effective in the diagnosis of AA, procalcitonin and RDW values are effective in the separation of perforated cases.
Çocuklarda akut apandisit tanısında laboratuvar bulgularının tanısal değeri
Keywords: acute appendicitis; alvarado score; C-reactive protein; in children; mean platelet volume; neutrophil-to-lymphocyte ratio; procalcitonin; red cell distribution